Non-isothermal crystallization kinetics of syndiotactic polystyrene polystyrene functionalized SWNTs nanocomposites (eXPRESS Polymer Letters)
Non-isothermal crystallization kinetics were characterized by using differential scanning calorimetry (DSC) analysis on neat semicrystalline syndiotactic polystyrene (sPS) and its nanocomposites with polystyrene (PS) functionalized full-length single walled carbon nanotubes (SWNT-PS), which was prepared by copper (I) catalyzed click coupling of alkyne-decorated SWNTs with well-defined, azide-terminated PS. The crystallization behavior of neat sPS polymer was compared to its SWNT based nanocomposites. The results suggested that the non-isothermal crystallization behavior of sPS/SWNT-PS nanocomposites depended significantly on the SWNT-PS content and cooling rate. The incorporation of SWNT-PS caused a change in the mechanism of nucleation and the crystal growth of sPS crystallites, this effect being more significant at lower SWNT-PS content. Combined Avrami and Ozawa analysis was found to be effective in describing the non-isothermal crystallization of the neat sPS and its nanocomposites. The activation energy of sPS determined from non-isothermal data decreased with the presence of small quantity of SWNT-PS in the nanocomposites and then increased with increasing SWNT-PS content.